1991
DOI: 10.1109/3.89946
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of bound electron nonlinear refraction in solids

Abstract: A two-band model is used to calculate the scaling and spectrum of the nondegenerate nonlinear absorption Aa(w,; wJ. From this, the bound electronic nonlinear refractive index n2 is obtained using a Kramers-Kronig transformation. We include the effects of two-photon and Raman transitions and the ac Stark shift (virtual band blocking). The theoretical calculation for n, shows excellent agreement with measured values for a five order of magnitude variation in the modulus of n2 in semiconductors and wide-gap opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

51
537
1
10

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,007 publications
(599 citation statements)
references
References 44 publications
51
537
1
10
Order By: Relevance
“…In general, bulk semiconductors change the sign of n 2 above their half E G values. 28 However, in Fig. 2 we observe that, in Ge NCs, this takes place at even beyond E G ; for the D = 2.25 and 3 nm NCs, the emergence of resonance is seen to develop, which can possibly reproduce this sign change at lower than E G values for the larger NCs.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…In general, bulk semiconductors change the sign of n 2 above their half E G values. 28 However, in Fig. 2 we observe that, in Ge NCs, this takes place at even beyond E G ; for the D = 2.25 and 3 nm NCs, the emergence of resonance is seen to develop, which can possibly reproduce this sign change at lower than E G values for the larger NCs.…”
Section: Resultsmentioning
confidence: 87%
“…Hence, as the figure of merit, n 2 / ␤ is proposed. 28 In our previous work, we have observed that the Si NCs possess much superior figure of merit parameters compared to bulk Si. 27 Figure 5 shows that Ge NCs closely resemble the results of Si NCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the two-band model with a simple direct bandgap, Sheike-Bahae et al [14] have calculated the dispersion and band-gap scaling of the bound electronic Kerr nonlinearity, n 2 , in solids. The nonlinear refractive index is given by…”
Section: Resultsmentioning
confidence: 99%
“…For CdSe illuminated with a wavelength of 1.06 µm, γ is found experimentally to be -1.47 × 10 -30 W µm -2 . 20 The theoretical estimates for polarizability are depicted in Figure 4, the black squares are based on simply using n as the refractive index in eq 2, and the black circles are based on using n c , which includes the nonlinear correction. As apparent from Figure 4, the absorption process that gives rise to the nonlinear contribution to the refractive index has only a minor effect on the total polarizability, R/ε 0 , found from eq 2.…”
mentioning
confidence: 99%